Hornschuchia (Annonaceae), an endemic and threatened genus from the Brazilian Atlantic Forest - Vilela, Lucas; de Carvalho Lopes, Jenifer (European Journal of Taxonomy, 2022)
The South American Atlantic Forest is a biodiversity hotspot, and a relevant area for conservation due to its high level of endemism and great loss of habitat. One of its endemic taxa is the genus Hornschuchia (Annonaceae), including 12 species that occur from the State of Rio de Janeiro to Pernambuco in Brazil. The last taxonomic treatment of Hornschuchia was carried out 27 years ago. Since that time, two new species have been described and new specimens of known species have been collected, expanding our knowledge about the morphology and distribution of the genus. Hornschuchia, as an endemic genus in a threatened environment, deserves special attention. For this reason, we updated the taxonomic treatment of Hornschuchia, including the recently described species in the key, preparing illustrations, updating the descriptions of the species, clarifying and correcting information regarding the historical and type collections, providing preliminary conservation statuses, and analyzing patterns of endemism and richness for the genus. One species is preliminarily assessed as Critically Endangered, nine are Endangered, one is Vulnerable and one is of Least Concern. The coast of Bahia is a priority place for conservation for Hornschuchia as its center of species diversity.